The investor behavior on extreme situations of speculation and crash: a game theory approach based on the iterated prisoner’s dilemma - Silva, Rui Miguel Constantino da (2017)
The present dissertation aims to develop an analysis to the investor behavior on situations of speculation and crash on stock markets. An approach to the main investor behavioral features is made, mainly the ones related with cognitive and decision-making questions in order to obtain an individual and the aggregate behavioral profile of the investor on situations of extreme events. Thus, the present work is structured on two main parts. The first one is related to the literature review about the definition of the investor, mainly considering questions linked to rationality, information processing, motivations and needs and properties which define the decision making process; contextualized the main problem of the study. In this part the events that leaded to the stock crashes of 1929 and 2000 were selected. On the second part (from Chapter 4) a concrete analysis to the behavior of the investor is made for these events through game theory, particularly, making use of the Iterated Prisoner’s Dilemma model to a sub-game that possesses as the main problem the existence, between players, of cooperation attitudes, aiming the maintenance of their positions or even their investments on overvalued assets, which are the main cause of the speculative bubble, and defection, which implies the opposite posture. The possibility of cooperation among the agents is inferred for a brief period of time, being demonstrated also that the equilibria were unstable for these situations.